Urban flood mitigation strategies using geospatial tools: A practical approach for cities and towns of the developing world - Kumar, Narendar (London Routledge, 2024)
This book balances the theoretical with empirical approaches to form a unique standpoint on the various challenges and possible solutions to urban flooding in India. Through a study of major urban flood incidents, this book analyzes the factors which contribute to the rising risk of flooding with increasing urbanization, population dynamics, growth, and urban sprawl, with particular focus on the cities of Chennai, Mumbai, and Hyderabad in India. It also examines disaster governance on urban floods and legislative prospects of flood disasters through discussions on standing acts, United Nations (UN) directives, and internationally adopted practices and actions, which are applicable in the Indian context.
Keywords: Hazards and disasters; Urban geography; Sustainable architecture